2000
DOI: 10.4049/jimmunol.164.2.712
|View full text |Cite
|
Sign up to set email alerts
|

uPA/uPAR System Is Active in Immature Dendritic Cells Derived from CD14+CD34+ Precursors and Is Down-Regulated upon Maturation

Abstract: We recently described a subset of peripheral CD14+CD34+ cells able to migrate across endothelial cell monolayers and differentiate into immunostimulatory dendritic cells (DC). In this paper we show that immature DC derived from CD14+CD34+ precursors are also capable of reverse transendothelial migration and extracellular matrix (ECM) invasion using the urokinase plasminogen activator receptor (uPAR). We found that these cells respond to macrophage-inflammatory protein (MIP)-1α, enhancing their ability to invad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The cell type where these pathways are activated may have different biological outcomes such as migration and motility, growth and differentiation, etc. (Yebra et al, 1996;Stepanova et al, 1997;Dumler et al, 1999;Ferrero et al, 2000). As the binding of uPA to uPAR is critical for the activation of Erk, we can hypothesise that high level of endogenous uPA expressed and secreted by WT and mock-transfected HCT116 cells can bind to excess uPAR on the cell surface, and thereby regulate the steady-state level of active Erk.…”
Section: Discussionmentioning
confidence: 99%
“…The cell type where these pathways are activated may have different biological outcomes such as migration and motility, growth and differentiation, etc. (Yebra et al, 1996;Stepanova et al, 1997;Dumler et al, 1999;Ferrero et al, 2000). As the binding of uPA to uPAR is critical for the activation of Erk, we can hypothesise that high level of endogenous uPA expressed and secreted by WT and mock-transfected HCT116 cells can bind to excess uPAR on the cell surface, and thereby regulate the steady-state level of active Erk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DA-3/sec cells most likely recruit less MDSCs due to their down-regulation of uPA. It has previously been shown that uPA is critical for macrophage chemotaxis, 38 basophil chemotaxis, 39 migration, and invasion of immature DCs, 40 and uPA Ϫ/Ϫ mice fail to recruit inflammatory cells to sites of infections. 41 Furthermore, it has been shown in human neutrophils that uPA can form a trimolecular complex with its receptor, uPAR, and the CD11b integrin, resulting in enhanced adhesion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…However, pro-uPA consistently inhibited virus production in a lymphoid organ-tissue culture system, in which T cells are mostly in a resting state (39) but are, nevertheless, permissive for both R5 and X4 HIV infection (40) without requiring in vitro activation (41,51).…”
Section: Discussionmentioning
confidence: 99%